Association of ABO blood types and novel obesity markers in healthy adolescents - Nazeem Ishrat Siddiqui; Ajay Soni; Sarfaraz Alam Khan (Journal of Education and Health Promotion, 2019)
INTRODUCTION: Association of ABO blood type with body mass index (BMI) was explored in the past studies, but literature on association of novel obesity markerssuch as total body fat and lean body mass (LBM) is scarce. The present study aimed to evaluate the relationship of ABO blood types with novel obesity markers in normal adolescents. MATERIALS AND METHODS: A cross-sectional study was done on 387 medical students. Bio-impedance analysis (BIA)-derived novel obesity markers such as body fat percent (BFP) and lean body mass (LBM) were recorded. Blood typing was done using slide-agglutination method. Mean and SD were calculated; analysis of variance and Chi-square (χ2) correlation were used to determine the relationship between ABO blood types and obesity markers. RESULTS: Highest propensity for BFP and LBM was seen in blood groups AB and B (25.09 ± 8.92 and 44.45 ± 6.91) respectively. Highly significant (P < 0.001) differences were observed in the values of BFP and LBM in normal and obese participants across ABO blood types. Prevalence of obesity did not show significant relationship (χ2 = 2.069; P = 0.913) with ABO blood types. CONCLUSIONS: Unlike BMI, novel obesity markers (BFP and LBM) significantly differ across ABO blood groups in normal and obese population. The findings suggest that ABO blood type might have role in determining body composition. This will be helpful in recognition of the participants at the risk of obesity on the basis of their blood groups.